Pemberdayaan Perempuan Dalam Meningkatkan Kesejahteraan Ekonomi Keluarga - bertha beloan; Rostini; Nisma Iriani; Nurmillah Ilyas; Andi Jamaluddin; Harniati; Syahribulan (ADPERTISI, 2023)
AbstractThe role of women today can no longer be underestimated, because it is undeniable that the current public world has accepted a